Karakteristik Sediaan Lotion Dengan Komposisi Rumput Laut Merah (Euchema spinosum) Yang Berbeda - Mesang, Selni; Henggu, Krisman Umbu (Universitas Negeri Gorontalo, 2025)
The seaweed E. spinosum is a species that is quite abundant in East Sumba Regency, and its use is still very limited. This seaweed is known to have a high carrageenan content and can be used as a stabilizer and emulsifier in cosmetic products, such as body lotion. This research examines different E. spinosum formulas (5%, 10%, 15%) on the characteristics of the produced body lotion. The results showed that body lotions with varying concentrations of E. spinosum seaweed (0%, 5%, 10%, and 15%) had an average pH value ranging from 7.6 to 8.4 and an IC50 value ranging from 2.597 to 4.540. However, they did not meet antioxidant standards for cosmetic preparations. The body lotion exhibited homogeneity issues, containing non-uniform seaweed granules. Different concentrations of E. spinosum did not have a significant effect on color, aroma, or texture. However, they did impact the liking level and absorption capacity. In general, panelists preferred body lotion treated with a 15% concentration of E. spinosum due to its bright color, thick texture, even absorption and distribution, and fragrant aroma.